An alternative method for continuous property measurement during depth-sensing indentation. (10th May 2007) - Chiu, Y.L.; Feng, G.; Tang, B.; Ngan, A.H.W.
Based on the Oliver-Pharr framework, an iteration scheme is proposed to continuously evaluate the hardness during monotonic loading in nanoindentation. The new method was applied to measure the hardness of various crystalline materials including Al, Cu, Ni3Al(Cr, B) and MgO, where an obvious Indentation Size Effect (ISE) was observed. In a-Se and PP, no ISE was observed when using exponential loading schemes at constant strain rates. The new method therefore produced the correct ISE behaviours in various materials under different loading situations.